Prevalence, Severity of Dental Caries and Need for Restorative Treatment in Schoolchildren Aged 6 to 12 Years in Sample of Iraqi Children - Noor Sabah Noori; Mina Amer Kamal; Nareman Muhannad Zaidan (Open Journal of Physicians and Surgeons, 2024)
Background: Dental caries is the most chronic non-communicable disease prevalent in Iraq and the world, affecting both primary dentition as a permanent, representing an important challenge for the health public. Objective: To determine the prevalence and severity of caries and the need for treatment of a population representative of schoolchildren from 6 to 12 years. Material and Method: Design and sample of the study The sample of this study represents the universe of schoolchildren of the Baghdad province of the period between 2020 and 2023. Seven schools were included, one from the high socioeconomic stratum, representing 20.78% of the sample, five from the middle stand being 53.71% and one of the lower stratum with 25.50% of the sample. These institutions did not have additional preventive interventions to those delivered in the regular dental programs of the Ministry of Health. Results: The prevalence of dental caries was 24.5% for permanent teeth and 47.8% for primary teeth. The DMFT index was 0.48, while the PMFT value was 1.67. The SiC value on DMFT was 1.45, but on dmft it was 4.52. Permanent teeth and primary dentition necessitated 167 and 689 hours of restorative treatment individually. Conclusions: The occurrence and extent of dental caries in school children aged 6 to 12 years in the Province of Baghdad were lower than previously documented rates and below the recommended levels set by international organizations. The restoration of the broken foundation in this sample will require 856 hours.